2015
DOI: 10.4265/bio.20.71
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Legionella</i> Species in Environmental Water by the Quantitative PCR Method in Combination with Ethidium Monoazide Treatment

Abstract: We detected Legionella species in 111 bath water samples and 95 cooling tower water samples by using a combination of conventional plate culture, quantitative polymerase chain reaction qPCR and qPCR combined with ethidium monoazide treatment EMA-qPCR methods. In the case of bath water samples, Legionella spp. were detected in 30 samples by plate culture, in 85 samples by qPCR, and in 49 samples by EMA-qPCR. Of 81 samples determined to be Legionella-negative by plate culture, 56 and 23 samples were positive by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In general, EMA/PMA-qPCR reduces the detection rates compared to conventional qPCR, but demonstrates equal or higher detection rates and cell counts relative to culturing due to inclusion of VBNC cells (Delgado-Viscogliosi et al, 2009; Inoue et al, 2015; Mansi et al, 2014). The effectiveness of EMA/PMA-qPCR is associated with a variety of factors, such as dye selection and dosage (Chen and Chang, 2010; Yanez et al, 2011), incubation time (Yanez et al, 2011), sample types (Inoue et al, 2015), target-cell loads and background flora (Gensberger et al, 2013; Slimani et al, 2012), as well as characteristics of target microorganisms (e.g., bacterial or eukaryotic cells (Fittipaldi et al, 2011)). Therefore, optimization processes and extra adaptation steps for each sample and/or microorganism type may be needed prior to application of EMA/PMA-qPCR.…”
Section: Detection Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, EMA/PMA-qPCR reduces the detection rates compared to conventional qPCR, but demonstrates equal or higher detection rates and cell counts relative to culturing due to inclusion of VBNC cells (Delgado-Viscogliosi et al, 2009; Inoue et al, 2015; Mansi et al, 2014). The effectiveness of EMA/PMA-qPCR is associated with a variety of factors, such as dye selection and dosage (Chen and Chang, 2010; Yanez et al, 2011), incubation time (Yanez et al, 2011), sample types (Inoue et al, 2015), target-cell loads and background flora (Gensberger et al, 2013; Slimani et al, 2012), as well as characteristics of target microorganisms (e.g., bacterial or eukaryotic cells (Fittipaldi et al, 2011)). Therefore, optimization processes and extra adaptation steps for each sample and/or microorganism type may be needed prior to application of EMA/PMA-qPCR.…”
Section: Detection Methodsmentioning
confidence: 97%
“…These intercalating dyes are intended to enter damaged cell membranes and covalently bind to DNA after photo activation, preventing downstream PCR amplification of DNA from membrane-compromised cells. Several studies have indicated promise of an EMA/PMA-based qPCR method for Legionella (Adela Yanez et al, 2011; Chen and Chang, 2010; Delgado-Viscogliosi et al, 2009; Inoue et al, 2015; Mansi et al, 2014; Slimani et al, 2012), mycobacteria (Lee et al, 2015; Nocker et al, 2007), P. aeruginosa (Gensberger et al, 2013, 2014), and Acanthamoeba (Chang et al, 2013) cells by testing against heat-treated, chlorine-treated cells and/or environmental water samples (e.g. drinking water, spa water, swimming pool water) as controls.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Another promising strategy to assess cell viability relies on the use of nucleic acid intercalating dyes such as ethidium monoazide (EMA) or propidium monoazide (PMA) in combination with specific PCR amplification (Elizaquível et al 2014;Inoue et al 2015;Lee et al 2015;Cattani et al 2016). This method is based on the membrane integrity of cells, as intact cell membranes (i.e., viable cells) are not permeable to these dyes contrarily to compromised cell membranes (i.e., dead cells).…”
Section: Introductionmentioning
confidence: 99%
“…After treatment with EMA using the Viable Legionella Selection Kit for PCR Ver. 2.0 (Takara Bio) and LED CrossLinker 12 (Takara Bio), the DNA was extracted with Lysis Buffer for Legionella (Takara Bio) [38]. All protocols were carried out according to the manufacturer's instructions.…”
Section: Ema-qpcrmentioning
confidence: 99%